2015
DOI: 10.4236/ojas.2015.52015
|View full text |Cite
|
Sign up to set email alerts
|

Compost Barns for Dairy Cows—Aspects of Animal Welfare

Abstract: Compost barns for dairy cows are showing increased popularity also in Central Europe. A compost barn is used mainly as a two-area system with a bedded lying area and a solid feeding alley. Sawdust or dry fine wood shavings or wood chips are mostly used as bedding material, which has to be stirred twice a day. Stirring aerates and mixes faeces and urine into the bedding material, the mixture decomposes by means of aerobic microorganisms. A joint research project between the Agricultural Research and Education C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…These species are the most common causative agents of digital dermatitis in dairy cattle (Biemans et al, 2018). Ofner-Schröck et al (2015) found a lameness prevalence of 25.4% in CBP and noted that this percentage is significantly lower than results obtained in a previous study including FS barns (45.7%). More recently, Burgstaller et al (2016) found no significant differences in lameness prevalence between cows housed in CBP and FS (18.7% vs. 14.9%).…”
Section: Lameness and Hock Lesionsmentioning
confidence: 65%
See 3 more Smart Citations
“…These species are the most common causative agents of digital dermatitis in dairy cattle (Biemans et al, 2018). Ofner-Schröck et al (2015) found a lameness prevalence of 25.4% in CBP and noted that this percentage is significantly lower than results obtained in a previous study including FS barns (45.7%). More recently, Burgstaller et al (2016) found no significant differences in lameness prevalence between cows housed in CBP and FS (18.7% vs. 14.9%).…”
Section: Lameness and Hock Lesionsmentioning
confidence: 65%
“…However, the CBP housing system has garnered strong global interest in the past decade. Experience with CBP from the United States (Janni et al, 2007;Barberg et al, 2007a;Black et al, 2013), Canada (LeBlanc andAnderson, 2013), Israel (Klaas et al, 2010), Denmark (Svennesen et al, 2014), the Netherlands (Galama, 2014), Austria (Ofner-Schröck et al, 2015;Burgstaller et al, 2016), Switzerland (Ghielmetti et al, 2017), Spain (Astiz et al, 2014), Italy (Leso et al, 2013), Brazil (Fávero et al, 2015a), Japan (Saishu et al, 2015), and South Korea (Galama et al, 2011) has been reported in the literature. Although all CBP worldwide share some similar characteristics, notable differences can be found among the systems developed in different countries and climates.…”
Section: Different Types Of Cultivated Pack Barnsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last few years, the CBP has been widely used in Brazil, especially in the south region, aiming to improve cattle comfort and longevity and to reduce somatic cell count (SCC) in milk (Black et al, 2013), and thus improving milk yield (Ofner-Schröck et al, 2015;Pilatti and Vieira, 2017). However, because it is a new housing system in Brazil, it still presents some challenges regarding the correct management of the compost bed, which directly and indirectly interferes in milk quality (Pilatti and Vieira, 2017).…”
Section: Introductionmentioning
confidence: 99%